Biomedical Promise of Sustainable Microwave-Engineered Symmetric Curcumin Derivatives - Cristina Doina Niţu; Maria Mernea; Raluca Ioana Vlasceanu; Bianca Voicu-Balasea; Madalina Andreea Badea; Florentina Monica Raduly; Valentin Rădiţoiu; Alina Rădiţoiu; Speranta Avram; Dan F. Mihailescu; Ionela C. Voinea; Miruna Silvia Stan (MDPI AG, 2024)
Curcumin is a polyphenol of the Curcuma longa plant, which can be used for various medicinal purposes, such as inflammation and cancer treatment. In this context, two symmetric curcumin derivatives (D1-(1E,6E)-1,7-bis(4-acetamidophenyl)hepta-1,6-diene-3,5-dione and D2-p,p-dihydroxy di-cinnamoyl methane) were obtained by the microwave-based method and evaluated for their antitumoral effect on human cervix cancer in comparison with toxicity on non-tumoral cells, taking into account that they were predicted to act as apoptosis agonists or anti-inflammatory agents. The HeLa cell line was incubated for 24 and 72 h with a concentration of 50 μg/mL of derivatives that killed almost half of the cells compared to the control. In contrast, these compounds did not alter the viability of MRC-5 non-tumoral lung fibroblasts until 72 h of incubation. The nitric oxide level released by HeLa cells was higher compared to MRC-5 fibroblasts after the incubation with 100 μg/mL. Both derivatives induced the decrease of catalase activity and glutathione levels in cancer cells without targeting the same effect in non-tumoral cells. Furthermore, the Western blot showed an increased protein expression of HSP70 and a decreased expression of HSP60 and MCM2 in cells incubated with D2 compared to control cells. We noticed differences regarding the intensity of cell death between the tested derivatives, suggesting that the modified structure after synthesis can modulate their function, the most prominent effect being observed for sample D2. In conclusion, the outcomes of our in vitro study revealed that these microwave-engineered curcumin derivatives targeted tumor cells, much more specifically, inducing their death.